Serum Gamma Glutamyl Transferase Levels in Association with Lipids and Lipoproteins in Type 2 Diabetes Mellitus - D RajaRajeswari; T Sharmila Krishnan; M. Prasad Naidu; J N Naidu (International Journal of Medical Research, 2014)
Introduction: Serum gamma glutamyl transferase is widely used as a marker for alcohol induced liver disease. Recently it has gained importance due to its role in type2 diabetes mellitus. A raised serum gamma glutamyl transferase level indicates hepatic steatosis and visceral fat deposition, leading to insulin resistance and diabetes. In the present study we examined the association between serum gamma glutamyl transferase levels with lipids and lipoproteins in diabetes mellitus. Methodology: The study was carried out on 50 subjects with type2 diabetes mellitus and compared with 50 ages and sex matched healthy controls attending outpatient department of General Medicine, Narayana medical college, Nellore. Serum gamma glutamyl transferase was measured by calorimetric kinetic assay. Fasting blood sugar was measured by glucose oxidase method using automated analyzer. Serum triglycerides, total cholesterol and high density lipoprotein are measured by standard enzymatic procedures and low density lipoprotein by friedwald equation. Results: Serum gamma glutamyl transferase levels in diabetic cases were significantly elevated compared to normal healthy controls [p <0.001]. There was a positive correlation between gamma glutamyl transferase, lipids and low density lipoprotein and inverse correlation with high density lipoprotein (r=-0.298)]. Conclusion: Our results suggest a possible role of gamma glutamyl transferase in the pathophysiology and progression of type2 diabetes mellitus.